Development of a Synbiotic Beverage Enriched with Bifidobacteria Strains and Fortified with Whey Proteins - Baruzzi, Federico; de Candia, Silvia; Quintieri, Laura; Caputo, Leonardo; De Leo, Francesca (Frontiers in Microbiology, 2017)
The objective of this study was to develop a new synbiotic beverage evaluating the ability of some bifidobacteria strains to grow in this beverage which was fortified with whey proteins up to 20 g L-1, and enriched with 10 g L-1 of prebiotic inulin or resistant starch. The ability of Bifidobacterium strains to survive for 30 days at 4°C was evaluated in two synbiotic whey protein fortified beverages formulated with 2% of whey proteins and 1% of inulin or resistant starch. Microbial growth was significantly affected by the whey protein amount as well as by the kind of prebiotic fibre. Resistant starch promoted the growth of the Bifidobacterium pseudocatenulatum strain and its viability under cold storage, also conferring higher sensory scores. The development of this new functional beverage will allow to carry out in vivo trials in order to validate its pre- and probiotic effects.